2013
DOI: 10.1080/0371750x.2013.851622
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cordierite Powder from Blast Furnace Slag

Abstract: We report a new process of synthesizing cordierite powder from blast furnace (BF) slag developed by using sol-gel route. The phase transformation of dried gel calcined under different temperatures was investigated by XRD and FTIR. It was found that one complicated silicic acid-sulphuric solutions system containing cations of Al 3+ and Mg 2+ was formed as the precursor of the cordierite by acid treatment of the slag. Cordierite powders with -cordierite as the main crystalline phase can be obtained when dried g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They have found that 87 wt.% of the cordierite phase is developed in the system at 1350°C along with open porosity around 32.8% and flexural strength about 47.26 MPa. Xingrong et al (2013) [170] have utilized blast furnace slag for synthesizing cordierite powder. Cordierite phases are formed in the range of calcination temperature at 1200-1300°C.…”
Section: Cordieritementioning
confidence: 99%
“…They have found that 87 wt.% of the cordierite phase is developed in the system at 1350°C along with open porosity around 32.8% and flexural strength about 47.26 MPa. Xingrong et al (2013) [170] have utilized blast furnace slag for synthesizing cordierite powder. Cordierite phases are formed in the range of calcination temperature at 1200-1300°C.…”
Section: Cordieritementioning
confidence: 99%